Archaeology of the books of Samuel : the entangling of the textual and literary history - Hugo, Philippe.; Schenker, Adrian, 1939- (Vetus Testamentum, Supplements, 2010)
The books of Samuel are a key link in the history of the biblical text in so much as they are found at a crossroad where different textual traditions encounter each other (MT, LXX, Qumran). Recent research tends to consider that the textual criticism has to take into account the literary aspects which characterise the most ancient transmission of the text. This assessment asks a variety of new exegetical questions considered in this volume: Does the comparative analysis of the textual witnesses permit proving the existence of distinct literary editions? Which are the criteria to deem the literary nature of the variants? Which ideological and theological motives governed the modifications of a previous text? Is it possible to establish a relative chronology between the putative editions? The study of the most ancient history of the text opens an archeology of the monument that are the books of Samuel. The search for their ancient foundations and the bringing to light of later modifications, the consideration both of the restorations and of the ruins of the textual edifice all throw new light on the final construct and its theological significance.